Refining the Assessment of Entitlement in Romantic Relationships: The Sense of Relational Entitlement Scale—Revised (SRE-R) - Tolmacz, Rami; Lev-Ari, Lilac; Bachner-Melman, Rachel (Frontiers in Psychology, 2021)
Objective: A subjective sense of entitlement is strongly evoked in the context of romantic relationships. A pathological sense of entitlement results from believing a partner should fulfil all one’s needs and wishes (inflated) or that the expression of genuine needs is illegitimate (restricted). This study aimed to validate a revised, improved version of the Sense of Relational Entitlement scale entitled the Sense of Relational Entitlement scale – Revised (SRE-R). We hypothesized it would have good factor structure and convergent validity, and that attachment dimensions and relationship indices would predict both inflated and restricted subscales. Method: The SRE-R was completed by 854 Israeli adults (8.3% males) aged 31.94±8.02. A subset (n=629) also completed measures of attachment (ECR-S) and 447 completed measures of relational authenticity, pathological concern, and relational obsessions and compulsions. Results: CFA confirmed two factors, inflated and restricted sense of relational entitlement. Relational obsessive-compulsive symptoms and pathological concern predicted an inflated sense of entitlement, and attachment avoidance, pathological concern and authenticity in relationships predicted a restricted sense of entitlement. Discussion: The SRE-R is a valid and useful tool to assess sense of entitlement in romantic relationships and should be examined in diverse samples and cultures.